El Salvador Financial Sector Assessment Program Development Module : Public Banks - World Bank (World Bank, Washington, DC, 2017)
This Technical Note was prepared in the context of a World Bank Financial Sector Assessment Program (FSAP) mission in the Republic of El Salvador in March 2016. This FSAP Development Module focused on (i) financial systems issues, including competition and efficiency; (ii) financial inclusion and non-bank financial institution issues, (iii) public sector banks, (iv) financial system infrastructure, including payments, remittances transfers, and credit information systems; (v) capital market and private pensions development issues; and (iv) insurance. The Technical Note describes the background and current situation of the public sector and development banks, and continues with specific recommendations directly linked with the assessment and diagnosis performed. The document contains technical analysis and detailed information underpinning the FSAP assessment’s findings and recommendations. Further information on the FSAP program can be found at www.worldbank.org/fsap.